THERMAL AND ENERGY EFFICIENCY SOLUTIONS FOR NATURAL GAS COMPRESSION USING INDUSTRIAL AUTOMATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The paper presents as results a proportional–integral–derivative (PID) function developed for a programmable logic controller (PLC) used to protect a screw electro-compressor from its thermal energy and a complex PLC algorithm developed for ensuring energy efficiency. The operating mode of an electro-compressor can be imposed as manual mode or automatic mode and can be selected from a developed HMI screen. The algorithm behind both manual mode and automatic mode will be analyzed in the article. The efficiency of energy consumption will result from the variation analysis of the current consumed by the main electric motor that drives the compression unit. The oil temperature evolution will also be analyzed from the parameter records, which is kept under control from a thermal point of view by a custom parameterized PID function. It will be detailed in the article how this custom parameterization of the PID function was performed and what the implications are from the point of view of the thermal efficiency for the electro-compressor.
Keywords: Energy efficiency algorithm; Thermal efficiency; Screw electro-compressor; Programmable logic controller; Proportional integral derivative (PID); Variable speed drive